Environmental legislation of Ukraine: towards the european union approaches - Yakymenko, Igor; Dotsenko, Olena; Negretova, Victoria; Pobuta, Oleksandra; Grychenko, Maryna; Madzhd, Svitlana (My University, 2024)
Environmental legislation of Ukraine is an important part of national legislation and based on fundamental principles of sustainable development. These include some particular articles of the Constitution (the main law) of Ukraine (VRU, 1996), the Law of Ukraine on Environmental Protection (VRU, 1995), relevant articles of Code of Ukraine on Administrative Offenses (1984) and Criminal Code of Ukraine (VRU, 2001) and many others. Starting from 2014, Ukraine began the implementation of key elements of EU legislation in terms of the EU – Ukraine Association Agreement (AA, 2014). And according to the Cabinet of Ministry of Ukraine, currently Ukraine implemented about 80% of European Union legal norms into national legislation as for the environmental protection (CMU, 2024). Good example of effective implementation of the EU laws into the legislation of Ukraine is an adapting a new Law of Ukraine on Waste Management (2022), which introduces European principles and European hierarchy in waste management into Ukrainian legislation.

Екологічне законодавство України є важливою частиною національного законодавства та базується на фундаментальних засадах сталого розвитку. До них належать окремі статті Конституції (основного закону) України (ВРУ, 1996 р.), Закону України «Про охорону навколишнього природного середовища» (ВРУ, 1995 р.), відповідні статті Кодексу України про адміністративні правопорушення (1984 р.) та Кримінального кодексу України. України (ВРУ, 2001) та багато інших. Починаючи з 2014 року, Україна почала імплементацію ключових елементів законодавства ЄС в частині Угоди про асоціацію між Україною та ЄС (AA, 2014). А за даними Кабінету Міністрів України, наразі Україна імплементувала близько 80% правових норм Європейського Союзу в національне законодавство щодо охорони навколишнього середовища (КМУ, 2024). Гарним прикладом ефективної імплементації законодавства ЄС у законодавство України є адаптація нового Закону України «Про поводження з відходами» (2022), який запроваджує європейські принципи та європейську ієрархію у поводженні з відходами в українське законодавство.
Keywords: environmental legislation; sustainable development; legislation of Ukraine; кафедра екології та екоменеджменту; екологічне законодавство; сталий розвиток; законодавство України